2015
DOI: 10.1016/j.exer.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

The BALB/c mouse: Effect of standard vivarium lighting on retinal pathology during aging

Abstract: BALB/cJ mice housed under normal vivarium lighting conditions can exhibit profound retinal abnormalities, including retinal infoldings, autofluorescent inflammatory cells, and photoreceptor degeneration. To explore the sensitivity of the outer retina to cyclic lighting during aging, a cohort of BALB/cJ mice was evaluated with Scanning Laser Ophthalmoscopy (SLO), Spectral-Domain Optical Coherence Tomography (OCT) and conventional histopathology. Mice were bred and reared in a low-illuminance (extracage/intracag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 29 publications
2
46
0
Order By: Relevance
“…Specific anatomical sites within an animal, whether it is a mammal or fish, can be used to calibrate the instrument focus position (Bell et al, 2015). The VRI and the proximal cone mosaic, areas of significant native contrast within the retina, can be used to establish calibration endpoints.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific anatomical sites within an animal, whether it is a mammal or fish, can be used to calibrate the instrument focus position (Bell et al, 2015). The VRI and the proximal cone mosaic, areas of significant native contrast within the retina, can be used to establish calibration endpoints.…”
Section: Resultsmentioning
confidence: 99%
“…Both instruments enable non-invasive, in vivo assessment of ocular tissues from a multitude of animal species. In vivo assessments have previously demonstrated that abnormal phenotypes may arise in both mammals and zebrafish that are present prior to the initiation of experimental studies (Bell et al, 2015; Bell et al, 2012; Joshi et al, 2016; Mattapallil et al, 2012; Tschopp et al, 2010). Using these instruments to screen for baseline abnormalities will avoid the potential for unexpected, confusing and confounding experimental results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For reference, 250 lux is less than recommended for office working conditions by a European Union regulation [156] and 2500 lux could be measured at midday during an overcast day [157]. In fact, albino Balb/C mice and Sprague-Dawley rats have been reported to develop retinal degeneration even under vivarium conditions [18,19]. As albino strains are extremely sensitive for light damage, we strongly suggest housing them in the dimmest part of the laboratory animal facility (for instance, lowest rows of cage racks) whenever possible.…”
Section: Several Mouse Models Of Rarer Neurodegenerative Diseases Sumentioning
confidence: 99%
“…Albino mice and rats are well known for their poor vision, but they do still respond to visual pattern stimulation [15] and thus likely utilize their vision in a behaviorally meaningful way. However, vision in albino rodents may easily be lost upon acute bright light exposure [16,17], or chronic low light level exposure even at their standard vivarium [18,19].…”
mentioning
confidence: 99%